The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Earth Crust 2019
DOI: 10.5772/intechopen.85413
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Weakening and Embrittlement of Intact Hard Rocks in the Earth’s Crust at Seismic Depths as a Cause of Shallow Earthquakes

Abstract: Frictional stick-slip instability on pre-existing faults is well studied experimentally and considered as the general mechanism for shallow earthquakes. At the same time, post-peak properties of intact hard rocks under high confining stresses σ 3 corresponding to seismic depths of shallow earthquakes are still unexplored experimentally due to uncontrollable and violent failure of rock specimens even on modern stiff and servocontrolled testing machines. The lack of knowledge about post-peak properties of the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…This means that the specimen strength at these stages of failure is equal to τ fan , which is significantly lower than the frictional strength τ f . This stage of the postpeak rupture is classified as class III (Tarasov, 2019). When the fan crosses the specimen, the strength of the specimen increases and is determined by the residual frictional strength τ f .…”
Section: Postpeak Properties Of Rocks Caused By the Fan Mechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the specimen strength at these stages of failure is equal to τ fan , which is significantly lower than the frictional strength τ f . This stage of the postpeak rupture is classified as class III (Tarasov, 2019). When the fan crosses the specimen, the strength of the specimen increases and is determined by the residual frictional strength τ f .…”
Section: Postpeak Properties Of Rocks Caused By the Fan Mechanismmentioning
confidence: 99%
“…It was found that at a lower unloading rate, the stress-time curves take the form of an AEC curve, and for spontaneous rupture without servo-controlled unloading, they take the form of an AF curve. A more detailed consideration of the duality of the strength properties of hard rocks in the rupture process controlled by the fan mechanism is presented in the findings of Tarasov (2019).…”
Section: Postpeak Modulus and Postpeak Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…Accepting this fact, the models were simplified by presenting the future fault as consisting of "predetermined" slabs. A detailed description of the physical and mathematical models is presented in previous papers (Tarasov, 2010(Tarasov, , 2014(Tarasov, , 2017(Tarasov, , 2019Tarasov & Guzev, 2013;Tarasov & Randolph, 2011Tarasov et al, 2017). This paper uses The structure of the future fault consists of a row of "predetermined" slabs (tiles) inclined at an angle α 0 to the rupture plane.…”
Section: Physical and Mathematical Models Of The Fan Mechanismmentioning
confidence: 99%
“…Since the extraordinary features of the fan mechanism and the properties of rocks determined by it contradict the classic theories, the fan‐hinged approach was perceived with great difficulty and distrust. The problem is that in the brief papers published so far, it was impossible to present this extremely complex and extensive topic with clear arguments, reliable evidence, and detailed discussion (Tarasov, 2008, 2010, 2011, 2013, 2014, 2016, 2017, 2019; Tarasov & Guzev, 2013; Tarasov & Ortlepp, 2007; Tarasov & Potvin, 2013; Tarasov & Randolph, 2008, 2011, 2016; Tarasov & Sadovskii, 2016; Tarasov et al, 2016, 2017).…”
Section: Introductionmentioning
confidence: 99%